(Table) Foraminifera abundance and diversity in sediment Core MD02-2508, Baja California continental slope - Murdmaa, Ivar O; Kazarina, G H; Beaufort, Luc; Ivanova, Elena V; Emelyanov, Emelyan M; Kravtsov, Victor A; Alekhina, G N; Vasileva, V E (Supplement to: Murdmaa, IO et al. (2010): Upper Quaternary laminated sapropelic sediments from the continental slope of Baja California. Lithology and Mineral Resources, 45(2), 154-171, https://doi.org/10.1134/S0024490210020057, 2010)
Core MD02-2508 retrieved from the plateau of the continental slope off Baja California recovered a 40-m-thick section of sapropel (up to 15% Corg), calcareous clay, and diatom ooze with the age of 120 ka at the core bottom. The section is subdivided into three units: Unit I (Holocene) consists of the laminated sapropel; Unit II comprising oxygen isotope stages (MIS) 2, 3, and 4 is represented by homogeneous calcareous clay with interbeds of slightly siliceous sapropelic mud; and Unit III (MIS-5) is composed of laminated sapropelic diatom ooze. Laminated intervals are characterized by the intercalation of two lamina types: (1) dark-colored organic-rich laminae containing multi-species 'oceanic' diatom assemblages, as well as radiolarians, coccoliths, planktonic and benthic foraminifera; (2) lighter-colored laminae consisting of diatom ooze with the neritic colonial diatom assemblages commonly composed of one to three species of a single genera. The dark laminae are assumed to be generated within a high productivity zone over the slope, whereas light ones likely represent diatom mats produced by short-term boisterous phytoplankton blooms, possibly in the coastal upwelling.